2021
DOI: 10.14716/ijtech.v12i6.5250
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Irradiation of Cellulose Acetate-Polyethylene Glycol 400 Composite Membrane and Its Performance Test for Gas Separation

Abstract: Gas separation processes through membrane permeation have attracted the attention of researchers recently due to their promising applications. In this study, we modified the cellulose acetate (CA) membrane to improve the membrane performance of CO2/CH4 gas separation. The CA membrane was modified by adding polyethylene glycol (PEG) 400 as the carrier and N, N'methylenebisacrylamide (MBA) as the cross-linking agent. Gamma-ray from cobalt 60 was used as a reaction initiator with variation in irradiation doses. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…This is in line with previous studies, which showed that homopolymerization could occur at specific doses of gamma irradiation, inhibiting cross-linking and decreasing tensile strength. 27 So, this study proves that the 25 kGy irradiated group has a more optimal tensile strength than the 15 kGy irradiation because it has stable bonds between compounds. The dry condition PVAcollagen-HA composite membrane has a high tensile strength ranging from 27.28 AE 8.39 to 41 AE 1.40 MPa.…”
Section: Discussionmentioning
confidence: 55%
“…This is in line with previous studies, which showed that homopolymerization could occur at specific doses of gamma irradiation, inhibiting cross-linking and decreasing tensile strength. 27 So, this study proves that the 25 kGy irradiated group has a more optimal tensile strength than the 15 kGy irradiation because it has stable bonds between compounds. The dry condition PVAcollagen-HA composite membrane has a high tensile strength ranging from 27.28 AE 8.39 to 41 AE 1.40 MPa.…”
Section: Discussionmentioning
confidence: 55%
“…The solution casting method was used for the fabrication of the CA membrane. The preparation of the dope CA solution, which included solvent mixture ratio, temperature, stirring time, and wait-on time; the parameters were drawn from several studies, including Febriasari et [27][28][29][30] The CA dope solution was prepared by dissolving 15 wt% in a solvent containing acetone and DMAc in a 2 : 1 ratio. The solution was homogenized in a round sealed glass container by stirring for 24 h, until a clear solution was observed.…”
Section: Ca Membrane Fabricationmentioning
confidence: 99%
“…The use of room-temperature ionic liquid membranes, whether homogeneous or biphasic, revealed variations in permeability and selectivity, emphasizing the inuence of casting methods on membrane performance. [17][18][19][20] Different blends, such as CA/polysulfone(CA/PSF), CA/ thiazole-based polyimine (PM-4), CA/polyimide (PI), and CA/ Pebax, have notably enhanced gas separation performances. The incorporation of polymer has shown remarkable potential in enhancing the gas separation performance of membranes.…”
Section: Introductionmentioning
confidence: 99%